2014
DOI: 10.1186/1471-2458-14-1145
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of single motherhood on children in sub-Saharan Africa: a cross-sectional study

Abstract: BackgroundAlthough progress has been made toward reducing child morbidity and mortality globally, a large proportion of children in sub-Saharan Africa still die before age five and many suffer chronic malnutrition. This study investigated the influence of single motherhood on stunting and under-5 mortality in Cameroon, Nigeria and Democratic Republic of the Congo (DRC). Particular attention was paid to the influence of mother’s economic resources, parental care and health behaviour on the difference in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 86 publications
(129 reference statements)
5
44
0
Order By: Relevance
“…There is little prior research in this context to draw from to gain insight into this finding, particularly regarding school entry. Nevertheless, the results here confirm existing evidence that unmarried mothers have children with worse health outcomes (Clark & Hamplová, ; Gage, ; LeVine & LeVine, ; Ntoimo & Odimegwu, ). Unmarried mothers are more educated on average (DeRose et al, ), which may make them place more value on education for their children.…”
Section: Discussionsupporting
confidence: 89%
“…There is little prior research in this context to draw from to gain insight into this finding, particularly regarding school entry. Nevertheless, the results here confirm existing evidence that unmarried mothers have children with worse health outcomes (Clark & Hamplová, ; Gage, ; LeVine & LeVine, ; Ntoimo & Odimegwu, ). Unmarried mothers are more educated on average (DeRose et al, ), which may make them place more value on education for their children.…”
Section: Discussionsupporting
confidence: 89%
“…A lower survival rate was found among children of single mothers, possibly related to lower community support levels available to single mothers. Ntoimo and Odimegwu reported higher malnutrition and under‐five mortality rates in single‐mother households in Cameroon and suggested that the amount and quality of support that single mothers received from family members depended on cultural perceptions of single parenthood.…”
Section: Discussionmentioning
confidence: 99%
“…A nonresident father may invest little in his children because he feels reduced altruism toward them (a potential consequence of reduced interactions), he does not expect them to support him in his old age, or he has developed a close relationship with the children of a new partner (Cox, ). These drivers explain the frequently observed association between paternal absence from the household and negative outcomes for children in both Western (Anderson, Kaplan, & Lancaster, ; Case, Lin, & McLanahan, ; Emmott & Mace, ) and African (Anderson, Kaplan, Lam, & Lancaster, ; Clark & Hamplová, ; Ntoimo & Odimegwu, ; Thiombiano, LeGrand, & Kobiané, ) contexts.…”
mentioning
confidence: 97%